A Network Analysis of Peritraumatic Distress Reactions and Their Relation to Posttraumatic Stress Symptoms in People Exposed to Community Fires. Issue 4 (1st October 2020) - Greene, Talya; Palgi, Yuval; Dicker-Oren, Sheila Daniela; Gilbar, Ohad
Abstract : Objective : Research indicates that people who experience more intense peritraumatic reactions are at higher risk of subsequently developing PTSD. The study used network analysis to: 1) explore the network structure of peritraumatic distress reactions; 2) identify clusters of peritraumatic distress reactions; and 3) assess whether central items in the peritraumatic network have stronger network associations with subsequent posttraumatic stress symptoms (PTS). Method : A convenience sample of adults living in communities affected by large-scale community fires in Israel (November 2016) were recruited. Participants completed the 13-item peritraumatic distress inventory (PDI) within one month of the fires (n = 372), and the PTSD checklist for DSM-5 (PCL-5) four months after the fires (n = 199). Network analyses and exploratory graph analysis were conducted. Results : The PDI items were positively connected to each other in a network structure, which divided into two clusters: emotional reactions; and physical/somatic reactions along with guilt and shame. Loss of emotional control was the most central peritraumatic distress symptom. Highly central peritraumatic distress symptoms were not strongly associated with subsequent PTS; rather, physical reactions were most associated with PTS levels four months after the fires. Conclusions : Future studies should investigate targeting peritraumatic physical reactions as an early secondary prevention strategy for PTSD.